Integrated weed management strategies for soybean (Glycine max) with different planting dates - Raila, Salina (My University, 2025)
Weed is a major challenge in Kansas soybean production, particularly with rising herbicide resistance and a shift toward earlier planting dates. While farmers and researchers continue to adopt integrated weed management (IWM) strategies to address herbicide resistance, the changing trend of planting soybeans raises questions about its influence on weed control and yield. This thesis integrates findings from a field experiment and a farmer survey to evaluate how planting date, row spacing, and herbicide programs affect weed control and yield, and how these research insights align with on-farm practices. The field experiment was conducted at Kansas State University research sites in Manhattan, Ottawa, Scandia (2022–2023), and Parsons (2023), using a split-block design with four replications. Treatments included a factorial combination of two planting dates (early and normal) with two row spacings (38 cm and 76 cm) and four herbicide programs: two preemergence combinations, sulfentrazone + metribuzin and flumioxazin + metribuzin, followed by two postemergence applications: 2,4-D choline + glyphosate with or without S-metolachlor. One weed-free and one non-treated control plot were also included within each row spacing for comparison. Data were collected for visual weed control and percent light interception at four weeks after pre- and postemergence herbicide applications, weed biomass at the R7 stage of soybean, and soybean yield. Data were analyzed in R using ANOVA and Tukey’s HSD. Results indicated that early planting generally improved weed control, although its impact on yield was inconsistent and appeared to depend on environmental conditions. Narrow row spacing (38 cm) and the flumioxazin + metribuzin combination offered greater early-season weed suppression. Weed control after postemergence application was consistent across locations and planting times for all herbicide programs. To contextualize these results with current on-farm practices, a survey was conducted from 2024 to 2025 using an online questionnaire. Responses were collected from 60 soybean farmers across 37 Kansas counties, representing management of approximately 352 hectares respondent-1. The survey captured information on planting practices, problematic weed species, herbicide use, and decision-making processes. Findings revealed that Amaranthus species (pigweeds) are the most troublesome weeds. Early planting practices and adoption of IWM practices were also common among the respondents. IWM practices mostly included herbicide rotation, cover crops, and manipulating row spacing. Most respondents expressed satisfaction with their current strategies but also recognized the need for adjustments in response to increasing herbicide resistance and changing planting windows. Practices identified as effective in the current field study (early planting and narrow rows) were also commonly adopted by surveyed farmers. However, variable yield responses in the experiment suggest that effective weed control does not always translate into consistent yield benefits. In summary, both the field experiment and survey underscore the importance of weed control for Kansas farmers. While their strategies often align with research findings, continued Extension efforts are needed to address knowledge gaps in herbicide terminology and to support informed, site-specific decision-making.
Keywords: Weeds; Soybean; Early; Late; Planting; Survey